Omental Flap for Complex Sternal Wounds and Mediastinal Infection Following Cardiac Surgery - Li, Jing; Stadlbauer, Andrea; Floerchinger, Bernhard; Song, Zhiyang; Goetz, Markus; Lunz, Dirk; Schmid, Christof (The Thoracic and Cardiovascular Surgeon, 2022)
Introduction Omental flap (OF) is a traditional surgical option to counteract severe postcardiotomy mediastinal infection and to cover extensive sternal defects. We reviewed our experience with omental flap transfer (OFT) in various clinical circumstances, in which omentoplasty may be considered by cardiac surgeons.Methods Twenty-one patients, who underwent OFT from January 2012 to December 2021, were studied. The main indication was treatment of infected foreign material implants including vascular grafts and ventricular assist devices or prevention of its infection (16 patients). In five patients, an OFT was used to cure mediastinitis following deep sternal wound infection after median sternotomy.Results All patients had a high surgical risk with 3 ± 1.9 previous sternotomies and a mean Euro Score II of 55.0 ± 20.1. OF was successful in its prophylactic or therapeutic purpose in all patients, no complications related to the operative procedure were noted, that is, no early or late flap failure and no herniation of abdominal organs occurred. In-hospital mortality was six patients as three patients each died from multiple organ dysfunction syndrome and cerebral hemorrhage. All fifteen patients discharged demonstrated rapid recovery, complete wound healing without fistula, and no late gastrointestinal complications. The mean follow-up of 18 months was uneventful.Conclusion OFT seems to be an excellent solution for extensive mediastinal and deep sternal wound infections.
Keywords: mediastinitis; sternal wound infection; omentoplasty; omental flap transfer; sternal wound infection